Proyecto de creación de una Agencia de Viajes TOUR Operadora en la Ciudad de Riobamba con Certificación Turistica. - Núñez León, Daniel Fernando (2010)
This project aims to demonstrate the feasibility, technical and financial for its implementation in Riobamba. It has been produced with the use of methodologies and techniques used in the preparation and evaluation of productive projects, using criteria and quantitative parameters, which, in a coordinated way, have consistently help to achieve the desired level. The viability of this project is supported by the use of data from information sources of public and private sectors, which have been complemented by field research. Specifically, it has used information from the Ministerio de Turismo del Ecuador, I Tour of Riobamba Municipality, Internet, etc.